2013
DOI: 10.1186/1472-684x-12-35
|View full text |Cite
|
Sign up to set email alerts
|

'My dreams are shuttered down and it hurts lots’–a qualitative study of palliative care needs and their management by HIV outpatient services in Kenya and Uganda

Abstract: BackgroundDespite the huge burden of HIV in sub-Saharan Africa, there is little evidence of the multidimensional needs of patients with HIV infection to inform the person-centred care across physical, psychological, social and spiritual domains stipulated in policy guidance. We aimed to describe the problems experienced by people with HIV in Kenya and Uganda and the management of these problems by HIV outpatient services.MethodsLocal researchers conducted in depth qualitative interviews with HIV patients, care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…The observed association between psychological distress and HRQoL is consistent with prior research from the region [39]. Although the cause of psychological distress is beyond the scope of this study, the availability of ongoing counseling services to PLWHA has been shown to help mitigate the trauma or other psychological effects that may result from receiving an HIV diagnosis, navigating complex drug regimens, or isolation caused by stigma [40, 41]. Our findings that persons who initiated treatment late (CD4+ count <150 cells/µL or WHO stage 4) had lower HAT-QoL scores than those with less advanced disease were also consistent with studies performed in other resource-limited settings that showed a strong correlation between clinical indicators and HRQoL [2, 12].…”
Section: Discussionsupporting
confidence: 85%
“…The observed association between psychological distress and HRQoL is consistent with prior research from the region [39]. Although the cause of psychological distress is beyond the scope of this study, the availability of ongoing counseling services to PLWHA has been shown to help mitigate the trauma or other psychological effects that may result from receiving an HIV diagnosis, navigating complex drug regimens, or isolation caused by stigma [40, 41]. Our findings that persons who initiated treatment late (CD4+ count <150 cells/µL or WHO stage 4) had lower HAT-QoL scores than those with less advanced disease were also consistent with studies performed in other resource-limited settings that showed a strong correlation between clinical indicators and HRQoL [2, 12].…”
Section: Discussionsupporting
confidence: 85%
“…Studies were conducted in 24 countries in SSA with six studies including more than one country [45,64,84,95,124,130]. More than half the studies (59.7%) were conducted across South Africa, Uganda, Ethiopia and Kenya.…”
Section: Resultsmentioning
confidence: 99%
“…Just over half of the qualitative studies conducted semi-structured in-depth interviews (IDIs) (49; 56.3%) [17,2022,26,27,29,3237,3943,4547,49,51,5460,62,63,65–67,6971,78,81,84,85,8790,9597,165] with their HIV-positive participants. Eighteen studies (20.7%) used focus group discussions (FDGs) [19,23–25,28,50,53,61,68,73,74,76,77,82,94,98,167,169], 16 used both IDIs and FDGs (18.4%) [18,30,31,38,44,52,64,72,75,79,83,86,92,93,99,170], one used free attitude interviews (FAIs) and FGDs (1.1%) [80], one used group sessions without more detail [168], one used IDIs and life history and illness narratives [48] and one used digital stories [91].…”
Section: Resultsmentioning
confidence: 99%
“…We also introduced Saunders's theory of "total pain" to appreciate problems from a patient-centered view (1). This was represented as P 2 S 2 , reflecting: physical, psycho-emotional, social, and spiritual or belief system to describe what we named "the 4-quadrant approach" to understanding PLWH needs (43). Use of these palliative constructs encouraged a systematic approach to patients.…”
Section: Core Contentmentioning
confidence: 99%